2022
DOI: 10.1126/sciadv.abk0428
|View full text |Cite
|
Sign up to set email alerts
|

The transmission game: Testing behavioral interventions in a pandemic-like simulation

Abstract: During pandemics, effective nonpharmaceutical interventions encourage people to adjust their behavior in fast-changing environments in which exponential dynamics aggravate the conflict between the individual benefits of risk-taking and its social costs. Policy-makers need to know which interventions are most likely to promote socially advantageous behaviors. We designed a tool for initial evaluations of the effectiveness of large-scale interventions, the transmission game framework, which integrates simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Consistent with this conceptualization, D shows high stability over 4 years, performs on par with most specific aversive traits in predicting the development of said trait (Zettler et al, 2021), and predicts many consequential outcomes in a variety of domains, including aggression, behavioral nonadjustment during the COVID-19 pandemic, cheating, crime, sexism, social preferences, vengeance, and violence (Bader et al, 2022; Bonfá-Araujo et al, 2023; Denissen et al, 2022; Dinić et al, 2023; Hilbig et al, 2023; Rudloff et al, 2023; Schrödter et al, 2021; Ścigała et al, 2021; Vize et al, 2021; Woike et al, 2022). Crucially, D has been shown to fully account for the aversive essence of specific aversive traits in that the latter typically do not explain incremental variance in aversive outcomes once controlling for D (Hilbig et al, 2023; Moshagen et al, 2018).…”
Section: The Dark Factor Of Personality (D)mentioning
confidence: 69%
“…Consistent with this conceptualization, D shows high stability over 4 years, performs on par with most specific aversive traits in predicting the development of said trait (Zettler et al, 2021), and predicts many consequential outcomes in a variety of domains, including aggression, behavioral nonadjustment during the COVID-19 pandemic, cheating, crime, sexism, social preferences, vengeance, and violence (Bader et al, 2022; Bonfá-Araujo et al, 2023; Denissen et al, 2022; Dinić et al, 2023; Hilbig et al, 2023; Rudloff et al, 2023; Schrödter et al, 2021; Ścigała et al, 2021; Vize et al, 2021; Woike et al, 2022). Crucially, D has been shown to fully account for the aversive essence of specific aversive traits in that the latter typically do not explain incremental variance in aversive outcomes once controlling for D (Hilbig et al, 2023; Moshagen et al, 2018).…”
Section: The Dark Factor Of Personality (D)mentioning
confidence: 69%
“…Previous studies have shown that merely reporting daily case numbers has little impact on behavioural change, including vaccination 52,53 . Our study found that reporting the number of COVID-19 report cases had a negative association with the primary vaccine doses uptake in P1 and P2, and the association with uptake of the booster dose disappeared in P3 and P4.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, behavioral health games model the social dilemma in health decisions resulting from the tension between individual and collective interests. For instance, previous research has adopted behavioral games to model the positive social externalities from getting vaccinated by increasing herd immunity (Chapman et al, 2012; Korn et al, 2020) or adhering to pandemic measures (van Baal et al, 2022; Woike et al, 2022). Recently, behavioral games have also been used to model the negative social externalities from overusing antibiotics by increasing AMR (Böhm et al, 2022; Santana et al, 2023).…”
Section: Delayed Prescribingmentioning
confidence: 99%